The concept of Causality between Philosophy and Science - Razzouk, Ibrahim; Hassan, Mahmoud (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The principle of causality is considered one of the most important philosophical and scientific principles that played a seminal role in developing scientific and epistemic research. This started with the commencement of philosophical thought. Since then the early philosophers attempted to look for the first causes that formed the universe and the real reasons that led to the phenomena and incidents happeningin it , Hence, the principle of causality helped to present a general comprehensive viewpoint about the universe. This viewpoint says that nature always undergoes fixed rules, phenomena becomes regular according to a certain system and that the hierarchy of these phenomena is linked with systems that have laws and certain causal liaisons . With the advancement of science and knowledge, it has become clear to scientists and thinkers that mind does not conclude laws save through a number of principles, one of which is the principle of causality. Thus, scientific experiment shows that phenomena are related to each other as the causesare related to the effects. This is explained through the principle of causality by which it is possible to derive conclusions of the general laws that rule the relationships between correlated phenomena , As a result of the causal theory, many philosophical and scientific concepts that are strongly related to the principle of causality emerged. Such concepts were that of necessity, inevitability and indeterminism which in its turn led to the emergence of many philosophical doctrines and scientific movements that contributed greatly to the scientific and epistemic sphere through the theories and problematic questions they posed and probed.